Real Exchange Rate Targeting Under Capital Controls : Can Money Provide a Nominal Anchor? - Montiel, Peter (IMF Working Papers; Working Paper ;, 1991)
This paper examines the issue of whether the money supply can serve as a nominal anchor for the domestic price level under real exchange rate targeting. When capital controls are perfect so that there is complete separation between official and unofficial markets for foreign exchange, the domestic inflation rate can be stabilized, but only at the expense of a widening gap between official and parallel market exchange rates. When cross - transactions between the two markets are permitted, the steady state of the model is identical to that of a model without capital controls and, hence, the money supply cannot serve as a nominal anchor for the price level in the long run. If capital controls are nevertheless maintained temporarily, and are known to be temporary, targeting the money supply fails to stabilize the rate of inflation even in the short run.